Antioxidants benefits in hepatitis C infection in the new DAAs era - Lozano Sepúlveda, Sonia Amelia; Rincón Sánchez, Ana Rosa; Rivas Estilla, Ana María (Asociación Mexicana de Hepatóloga, 2019)
Some of the evidence on whether antioxidant supplements are effective in treatment of liver diseases is contradictory. Here we perform a descriptive analysis of the available data in vivo and in vitro of the possible antiviral action and controversy of several antioxidant molecules against HCV.